2006
DOI: 10.1179/174592006x93851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief computer-assisted diabetes self-management intervention on dietary, biological and quality-of-life outcomes

Abstract: This relatively low-intensity intervention appealed to a large, generally representative sample of patients, was well implemented, and produced improvement in targeted behaviours. Implications of this practical clinical trial for dissemination are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(95 citation statements)
references
References 0 publications
1
93
0
1
Order By: Relevance
“…All of the studies had HbA 1c as an outcome measure and 11 studies (13)(14)(15)(16)(18)(19)(20)(22)(23)(24)(25) provided enough data to combine in a meta-analysis, as shown in Fig. 2.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the studies had HbA 1c as an outcome measure and 11 studies (13)(14)(15)(16)(18)(19)(20)(22)(23)(24)(25) provided enough data to combine in a meta-analysis, as shown in Fig. 2.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Participants in one study (14) were all Latin or Hispanic. Three studies (13,15,16) reported that .70% of participants were Caucasian or non-Hispanic white. In 13 studies, all participants had type 2 diabetes; 3 studies (12,17,18) included participants with both type 1 and type 2 diabetes; the percentage of participants with type 1 diabetes ranged from 19-26%.…”
Section: Descriptions Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14][15] Unfortunately, most of these studies do not address the mechanisms for maintenance of lifestyle change, nor do the studies have data points beyond 1 year postintervention.…”
Section: Background and Significancementioning
confidence: 99%